On the Epistemological Foundation of Ethics - Reinhard Hesse (اخلاق وحیانی, 2015)
The question of truth in both practical and theoretical reason is raised. And attempts to ignore it have not been compelling and efficient. Human access to truth is a complex process which, as Kant observed, that in addition to sensory data are needed to concepts such as causality. And concepts did not derive from the human individual effort but are the results of human culture and collective work. So our efforts to attain to knowledge is dependent on other people, and therefore, to the common mentality. This means that the role of "discourse" in our knowledge of the world; in other words, knowledge is achieved in a process of dialogue. Naturally, this process has conditions and laws that arises in the logic of dialogue. This set of rules forms an ethics of knowledge that is that a formal system of reference for conflict resolution. This code is applicable not only in access to knowledge but it can be extended to the field of individual and collective human actions to solve problems of human. That is how human to avoid violence and war leads to dialogue as a promising process for resolving human problems.